2019
DOI: 10.4162/nrp.2019.13.5.444
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the association between health-related and work-related factors among workers and metabolic syndrome using data from the Korean National Health and Nutrition Examination Survey (2016)

Abstract: BACKGROUND/OBJECTIVEThis study analyzed health-related factors for metabolic syndrome (Mets) among workers in South Korea.SUBJECTS/METHODSThis analysis included 4,666 adults aged 19–64 years to analyzed health-related risk factors for Mets from the Korean National Health and Nutrition Examination Survey (2016). The sociodemographic, working, health-related, and biochemical characteristics were presented as percentages (%) by chi-square tests. Multiple logistic regression analysis was performed to analyze the 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The incidence of obesity, diabetes, high blood pressure, and cardiovascular diseases among elderly people is high, and metabolic syndrome (MetS), a major risk factor for chronic diseases, is on the rise [ 5 ]. The Korean Society of Cardio Metabolic Syndrome reported that senior citizens aged >65 years had a MetS rate of about 35% [ 6 , 7 ]. The prevalence of MetS (obesity, high blood pressure, and elevated high-density lipoprotein cholesterol (HDL-C) levels), which is a risk factor for cardiovascular diseases, has been reported to be significantly higher among elderly people in Korea than in those in the United States and Europe [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of obesity, diabetes, high blood pressure, and cardiovascular diseases among elderly people is high, and metabolic syndrome (MetS), a major risk factor for chronic diseases, is on the rise [ 5 ]. The Korean Society of Cardio Metabolic Syndrome reported that senior citizens aged >65 years had a MetS rate of about 35% [ 6 , 7 ]. The prevalence of MetS (obesity, high blood pressure, and elevated high-density lipoprotein cholesterol (HDL-C) levels), which is a risk factor for cardiovascular diseases, has been reported to be significantly higher among elderly people in Korea than in those in the United States and Europe [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This way of working makes it easier for workers to gain weight. In the literature, several studies reported a statistically significant association between shift working and the risk of developing MetS [21]. Shift workers, although forming the majority of our study population, had a lower risk of developing MetS than day workers (16.3% vs 22.4%).…”
Section: Discussionmentioning
confidence: 54%
“…In a recent study, Kim and Yun pointed out that male day workers are at a higher risk of MS compared to male shift workers. The prevalence of MS among women was expressed in terms of sleep duration: women who slept more than eight hours per day had a higher risk of MS than those who slept less than six hours [ 27 ]. The results of these sleep-related risk factors in the cited studies differed with those in this study.…”
Section: Discussionmentioning
confidence: 99%